THE EFFETC OF GUIDED QUESTION TECHNIQUE ON STUDENTS WRITING SKILL OF DESCRIPTIVE TEXT AT EIGHT GRADE STUDENT OF MTS NEGERI PEMATANG SIANTAR - RIYANI HARAHAP, RAHMI (BRIGHT VISION Journal of Language and Education, 2022)
This study aims to determine the effect of guided question technique on student’s writing skill. The subject of research was students of SMP Satrya Budi Karang Rejo at eight grade. This research were used quasi experimental with pre-test and post-test design. In this design there was two groups, namely groups randomly selected experimental and control groups. The researcher were use two classes as sample in this research, they were VIII A that consisted 20 students of controlled  class,  namely  class  VIII  A  was  an  controlled  class  in  this  study  given  used conventional method. This research were used quantitative method.The result of the researcher were quite significant with the experimental class was   mean score of post-test is 81.65. The mode is the score who students’ most get in experimental class got